Iron status of hill tribe children and adolescent boys: A cross sectional study at a welfare center in Chiang Mai, Thailand - Porniammongkol,O. (Asian Network for Scientific Information, 2015)
Iron Deficiency Anemia (IDA) is one of the major public health problems worldwide. High prevalence of anemia has been found in the developing countries, including Thailand. The purpose of this study was to investigate the iron status of 181 hill-tribe school boys who lived in Wat Donchan Welfare Center (DWC), Chiang Mai, Thailand. A cross-sectional study was conducted in 2 groups of children which were divided by age (7-11 years and >11-15 years). Body weight and height of each child were measured. Anthropometric status was classified using CDC 2000 Growth chart reference by Weight for Age (W/A) and Height for Age (H/A). Hemoglobin (Hb) and serum ferritin (Ft) were analyzed as indicators for iron status. Student's t-test and Pearson correlation coefficient was used to determine the significant differences and the relationship between the 2 groups or parameters at p<0.05. Results showed that 32% and 60% of children and adolescents were under weight and stunted, respectively. Mean Hb in young children was 11.9±0.8 g/dL while in older children was 12.5±1.1 g/dL. The prevalence of anemia was 31% using only Hb as an indicator, while the prevalence of IDA was 12% and Iron Deficiency (ID) was 23% when using Hb and Ft as the indicators. Iron deficiency was a major cause of anemia in this group; 25% and 41% of anemic children in younger and older group, respectively. The study found that 8% of children had the thalassemia trait and 93% of them were anemic. It was suggested that anemia in these hill-tribe children might be associated with insufficient iron food sources, poor sanitation, poor hygienic practice and hemoglobinopathies. © Asian Network for Scientific Information, 2011.